Role of Accounting Information in Making Share Investment Decisions: A Survey of Investors in Nepalese Stock Market - Vaidya, Rashesh (Journal of Business and Social Sciences Research, 2021)
The paper surveyed the opinion of investors in the Nepalese stock market to assess their views on the role of accounting information for making share investment decisions. During NEPSE trading hours, a survey was conducted among investors at the broker’s office. The study reveals that Nepalese investors use accounting information to increase their capabilities and skills in the investment decision[1]making process and to predict the trend of the listed companies’ performance. The investors have given top[1]most priorities to ‘share capital’, ‘net profit after tax’, and ‘cash flow from investing activities’ under balance sheet, income statement, and cash flow statement, respectively. Furthermore, the study shows that investors attach great importance to financial indicators related to share prices, namely earnings per share (EPS) and dividend per share (DPS). Therefore, publicly traded companies should monitor and publish a list of the main financial indicators that investors pay attention to improve the credibility of their performance.